Microplastics as persistent and vectors of other threats in the marine environment: Toxicological impacts, management and strategical roadmap to end plastic pollution - Sameh S. Ali; Mohammed Hussein M. Alsharbaty; Rania Al-Tohamy; Michael Schagerl; Majid Al-Zahrani; Michael Kornaros; Jianzhong Sun (Environmental Chemistry and Ecotoxicology)
The myriad consumption of plastic regularly, environmental impact and health disquietude of humans are at high risk. Microplastics (MPs) represent a contemporary type of contamination that has permeated several environmental areas. MP pollution is already widespread in marine environments, leading to increased awareness over the past few decades. Multiple studies are being conducted to determine the source of MPs and their harmful impacts on marine life and, ultimately, human health. Thus, this paper rigorously analyzed the origin, accumulation, and detrimental impacts of MPs on the marine ecosystem. An increase in the death rate, a decrease in the rate of growth, and a reduction in the quantity of food ingested were the primary changes that occurred in marine organisms. The hydrophobic properties of MPs enable them to facilitate the formation of biofilms, which are referred to as the plastisphere. These biofilms have the capacity to transport chemicals that are frequently hazardous and may potentially infiltrate the food chain. The coronavirus 2019 (COVID-19) pandemic has significantly exacerbated the plastic and MP contamination in coastal and marine environments as a result of the improper management of personal protective equipment and explosive production. The most recent developments in environmental DNA (eDNA) are valuable tools for the detection and tracking of MP contamination in coastal and marine ecosystems. These technologies offer greater sensibility, efficacy, and involvement in the process. There are several measures and attempts that must be taken to address the MP pollution issues in the marine environment. The knowledge gained from this review will serve as a foundation for future marine MP research and management techniques.